Impact of climate change on birds at Biratnagar and its surroundings - Jha, Kanchan; Subba, Bharat Raj (Nepalese Journal of Biosciences, 2013)
DOI: http://dx.doi.org/10.3126/njbs.v2i0.7506 Nepalese Journal of Biosciences 2 : 158-159 (2012)